Ocean animal emergency [videorecording (DVD)] - Hickey, John Benjamin (WGBH Boston Video, 2008)
"Part emergency room, part rehab facility, and part research lab, the Marine Mammal Center in Sausalito, California means the difference between life and death for sick and injured ocean animals. Nova takes you inside this very special ER to witness the efforts of a renowned team of wildlife veterinarians as they fight to save their animal patients as well as to uncover the cause of a mysterious neurological illness plaguing marine mammals like California sea lions and harbor seal pups."--Nova website.